Masa Depan Bio Informatika : Mengubah Data Menjadi Terapi (International Forum of Researchers and Lecturers, 2025)
Bioinformatics is an interdisciplinary field that combines biology, computer science and statistics to analyze biological data and translate it into effective therapies. With technological advances, such as next-generation genetic sequencing, bioinformatics enables the development of personalized therapies based on an individual's genetic profile. This approach provides more effective treatment and reduces the risk of side effects. In addition, the integration of artificial intelligence (AI) accelerates big data analysis, predicts therapy response and identifies disease biomarkers. Despite challenges such as the need for big data infrastructure and ethical privacy issues, the outlook for bioinformatics is bright. Through global collaboration and a multi-omics approach, bioinformatics is expected to become a key foundation in future medical therapy innovation.